Living Intersections: Transnational Migrant Identifications in Asia - Plüss, Caroline; Chan, Kwok-bun. (Dordrecht : Springer Netherlands, 2012)
This book presents ground-breaking theoretical, and empirical knowledge to produce a fine-grained and encompassing understanding of the costs and benefits that different groups of Asian migrants, moving between different countries in Asia and in the West, experience. The contributors—all specialist scholars in anthropology, geography, history, political science, social psychology, and sociology—present new approaches to intersectionality analysis, focusing on the migrants’ performance of their identities as the core indicator to unravel the mutual constituitivity of cultural, social, political, and economic characteristics  rooted in different places, which characterizes transnational lifestyles. The book answers one key question: What happens to people, communities, and societies under globalization, which is, among others, characterized by increasing cultural disidentification?
Introduction: 1: Theorizing and Proving Intersectionality in Transnational Contexts: Caroline Plüss and Chan Kwok-bun -- Section One: Explaining Mobility and Inequality -- 2: A Returnee’s Hybridity: Its Upside and Downside: Chan Kwok-bun -- 3: Theorizing Immigrant Family Adaptation, Maladaptation, and Poverty: New Arrivals in Hong Kong from Mainland China: Chan Kwok-bun -- 4: Class, Migration, and Identity in a Philippine Village: Philip Kelly -- Section Two: Nation States, Social Networks and Emotional Spaces: 5: Social Strain and the Adaptive Behavior of Hong Kong Return Migrants: Chan Kwok-bun and Chan Wai-wan -- 6: The Role of the State in Transnational Migrant Identity Formation: A ‘Uniquely Singapore’ Experience?: Selina Lim -- Section Three: Transnational Positionalities and Cultural Capital: 7: Chinese-Singaporean Repeat Migrant Women: Transnational Positionalities and Social Inequalities: Caroline Plüss -- 8: Transnational Motherhood in the Making of Global Kids: South Korean Educational Migrants in Singapore: Yoonhee Kang -- 9: Becoming New Overseas Chinese: Transnational Practices and Identity Construction among the Chinese Migrants in Japan: Gracia Liu-Farrer -- Section Four: Locating Transnational Identifications -- 10: Identifying the Periphery: Challenging Citizenship, Nationality, and Identity on the Ogasawara Islands; David Chapman -- 11: Brokers of Nostalgia: Shan Migrant Public Spheres in Chiang Mai, Thailand: Amporn Jirattikorn -- 12: Identities and Decentered Transnational Linkages: Return Migrants in Hong Kong: Lucille Lok-sun Ngan -- Conclusion: 13: Living in the Intersections of Cultures, Societies, Emotions, Politics and Economies: Deterritorializing Culture: Caroline Plüss.
SpringerLink eBooks.
Keywords: Social sciences; Population; Social structure; Social inequality; Emigration and immigration; Social Sciences; Migration; Population Economics; Social Structure, Social Inequality; Migration